Analisis Aliran Material Dan Limbah Produksi Batik Cap Menggunakan Sankey Diagram (Studi Kasus: Batik Putra Laweyan) - Adiani, Andar Rahma, Ida Nursanti, ST., M.Eng.Sc (2017)
Batik is the one of industry in Indonesia which has great development, especially in Central Java, Batik industry can grow until 91,6%. The demand of Batik exactly will can increase the production capacity. The high demand of batik can give impact in high of production capacity. Inspite of, the production of batik through in traditional process, so they need the high energy and give the high waste for the effect, especially the using of water as the resources for colouring and washing process. So, from that problems is needed to identify amount of energy, material which is used in Batik Cap Production for knowing the part of production procces which have high the material, energy and waste. The method to draw the flow of material and waste is Sankey Diagram. Before doing the analyze using Sankey Diagram, is needed the kind of waste which is produced by in Batik Cap Production. This result show that the liquid waste is the highest, and the total amount of energy is 35.687 MJ, after analyze and giving the solution for the using of energy, amount of energy is decrease 82% and 73% for water. Keywords: Batik, Life Cycle Assesment, Limbah, Sankey Diagram